Źródła przemian we współczesnej homiletyce fundamentalnej - Twardy, Jan (Śląskie Studia Historyczno-Teologiczne, 2006)
The theological reflection flowing from the God’s revelation was always the base of the catholic homiletics. However, the retoric – especially recommendations concerning the methodics and the form of sermons – have dominated in it now and then. Polish manuals on homiletics from 19th and the first half of 20th century are the good examples of this opinion. In the first half of the past century – especially after the Second Vatican Council – the catholic homilets increased their interests as regards God’s word and the biblical kerygmat. The main reasons of the changes in the fundamental catholic homiletics of that period are: development of the biblical research and emphacizing of the kerygmatic theology, revival of lithurgy along with the speciall accentuation of God’s word, ecumenical dialogue arising from achievements of protestant theologians. As the crisis of preaching and nowadays still widening dechristianization have been evident, it was necessary to pay bigger attention to authentic God’s word which – when spread – has its redemptive efficiency. That is why the contemporary homiletics stands on the strong theological foundations; owing to this, it delivers the deep supernatural motivation either to the preachers, as well as to the listeners to God’s word. Numerous publications concerning this subject evidently confirm this fact.